Perancangan User Experience Aplikasi E-SAKIP (Elektronik Sistem Akuntabilitas Kinerja Instansi Pemerintah) menggunakan metode Human-Centered Design (Studi Kasus: Kabupaten Kepulauan Selayar) - Nur Aenun Marjan; Ahmad Afif Supianto; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
E-SAKIP is an electronic-based government institution performance accountability system used by every Indonesian government institution to report their performance. One of the regencies that implement SAKIP is Kepulauan Selayar Regency. Every institution in Kepulauan Selayar Regency has to report all their performance in a year. Manual reporting and unclear information regarding the report cause many institutions to be late in submitting the SAKIP report. These problems become the reason for the establishment of E-SAKIP user experience. This user experience research is carried, the research already have a high satisfaction score from user and it doesn't take a lot of time and money to implement the application in the future. The methodology used in this study was a Human-Centered Design, where this study was directly focused on the potential users of E-SAKIP. The final product, in the form of prototype high fidelity, used Adobe XD. The prototype results were conducted the usability test, time test using the System Usability Scale (SUS). The usability results were 100%, the time test was 375 seconds, and the SUS was 81,125. This can be stated that the success rate is good and acceptable. Thus, the prototype results have been tested according to the level of potential users' satisfaction.